Effect of activation of canonical Wnt signaling by the Wnt-3a protein on the susceptibility of PC12 cells to oxidative and apoptotic insults - Kawamoto,E.M. (2012)
Wnt proteins are involved in tissue development and their signaling pathways play an important role during embryogenesis. Wnt signaling can promote cell survival, which is beneficial for neurons, but could also lead to tumor development in different tissues. The present study investigated the effects of a Wnt protein on the susceptibility of a neural tumor cell line (PC12 cells) to the cytotoxic compounds ferrous sulfate (10 mM), staurosporine (100 and 500 nM), 3-nitropropionic acid (5 mM), and amyloid β-peptide (Aβ25-35; 50 µM). Cells (1 x 10(6) cells/mL) were treated with the Wnt-3a recombinant peptide (200 ng/mL) for 24 h before exposure to toxic insults. The Wnt-3a protein partially protected PC12 cells, with a 6-15% increase in cell viability in the presence of toxic agents, similar to the effect measured using the MTT and lactate dehydrogenase cell viability assays. The Wnt-3a protein increased protein expression of β-catenin by 52% compared to control. These findings suggest that Wnt signaling can protect neural cells against apoptosis induced by toxic agents, which are relevant to the pathogenesis of Alzheimer’s and Huntington’s diseases.